2018
DOI: 10.1101/490466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal immune activation causes age-specific changes in cytokine receptor expression in offspring throughout development

Abstract: Maternal infection is a shared environmental risk factor for a spectrum of neuropsychiatric disorders and animal models of maternal immune activation (MIA) exhibit a range of neuropathologies and behaviors with relevance to these disorders. In particular, MIA offspring show chronic, age-and region-dependent changes in brain cytokines, a feature seen in postmortem studies of individuals with neuropsychiatric disorders. These MIA-induced alterations in brain cytokines may index biological processes underlying pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
(123 reference statements)
1
3
0
Order By: Relevance
“…It showed that the expression of the receptor gene was particularly up-regulated at the beginning of synaptogenesis (P7) and declined during the peak of this process and spine formation (P14). These age-specific changes in the Cx3cr1 transcript level implicate MIA-induced microglial dysfunctions that trigger alterations in cortical networks [178]. The evidence seems to support the reports on impaired anatomical and functional connectivity in the cerebral cortex of patients with schizophrenia [179][180][181].…”
Section: Experimental Datasupporting
confidence: 80%
See 2 more Smart Citations
“…It showed that the expression of the receptor gene was particularly up-regulated at the beginning of synaptogenesis (P7) and declined during the peak of this process and spine formation (P14). These age-specific changes in the Cx3cr1 transcript level implicate MIA-induced microglial dysfunctions that trigger alterations in cortical networks [178]. The evidence seems to support the reports on impaired anatomical and functional connectivity in the cerebral cortex of patients with schizophrenia [179][180][181].…”
Section: Experimental Datasupporting
confidence: 80%
“…were identified. A significant, although preliminary observation in the context of schizophrenia-associated abnormalities implementing the MIA model with Poly I:C was also provided by Estes et al [178] in their preprint article.…”
Section: Experimental Datamentioning
confidence: 80%
See 1 more Smart Citation
“…Current evidence suggests that a combination of polygenic susceptibility and exposure to environmental risk during sensitive periods of brain development can impair neurodevelopment, and confer vulnerability to the development of MND [1][2][3][4][5] . Possible environmental risk factors for MND include intrauterine stressors, such as maternal bacterial and viral infections during pregnancy [6][7][8][9][10] .…”
mentioning
confidence: 99%